Rhinovirus-Induced Exacerbations of Asthma and COPD - Marc B. Hershenson (Scientifica)
Over the past two decades, increasing evidence has shown that, in patients with chronic airways disease, viral infection is the most common cause of exacerbation. This review will examine the evidence for viral-induced exacerbations of asthma and chronic obstructive lung disease and the potential mechanisms by which viruses cause exacerbations. Attention will be focused on rhinovirus, the most common cause of respiratory exacerbations. Exacerbations due to rhinovirus, which infects relatively few cells in the airway and does not cause the cytotoxicity of other viruses such as influenza or respiratory syncytial virus, are particularly poorly understood. While the innate immune response likely plays a role in rhinovirus-induced exacerbations, its precise role, either adaptive or maladaptive, is debated. Because current treatment strategies are only partially effective, further research examining the cellular and molecular mechanisms underlying viral-induced exacerbations of chronic airways diseases is warranted.